Efficacy of 8- and 4-Session Mindfulness-Based Interventions in a Non-clinical Population: A Controlled Study - Demarzo, Marcelo; Montero-Marin, Jesus; Puebla-Guedea, Marta; Navarro-Gil, Mayte; Herrera-Mercadal, Paola; Moreno-González, Sergio; Calvo-Carrión, Sandra; Bafaluy-Franch, Laura; Garcia-Campayo, Javier (Frontiers in Psychology, 2017)
Background Many attempts have been made to abbreviate mindfulness programmes in order to make them more accessible for general and clinical populations while maintaining their therapeutic components and efficacy. The aim of this study was to assess the efficacy of an 8-week mindfulness-based intervention (MBI) programme and a 4-week abbreviated version for the improvement of well-being in a non-clinical population. Method A quasi-experimental, controlled, pilot study was conducted with pre-post and 6-month follow-up measurements and three study conditions (8- and 4-session MBI programmes and a matched no-treatment control group, with a sample of 48, 46 and 47 participants in each condition, respectively). Undergraduate students were recruited, and mindfulness, positive and negative affect, self-compassion, resilience, anxiety and depression were assessed. Mixed-effects multi-level analyses for repeated measures were performed. Results The intervention groups showed significant improvements compared to controls in mindfulness and positive affect at the two- and six-month follow-ups, with no differences between 8-session vs. 4-session programmes. The only difference between the abbreviated MBI vs. the standard MBI was found in self-kindness at six months, favouring the standard MBI. There were marginal differences in anxiety between the controls vs. the abbreviated MBI, but there were differences between the controls vs. the standard MBI at two- and six-months, with higher levels in the controls. There were no differences in depression between the controls vs. the abbreviated MBI, but differences were found between the controls vs. the standard MBI at two- and six-months, favouring the standard MBI. There were no differences with regard to negative affect and resilience. Conclusion To our knowledge, this is the first study to directly investigate the efficacy of a standard 8-week MBI and a 4-week abbreviated protocol in the same population. Based on our findings, both programmes performed better than controls, with similar effect size. The efficacy of abbreviated mindfulness programmes may be similar to that of a standard MBI programme, making them potentially more accessible for a larger number of populations. Nevertheless, further studies with more powerful designs to compare the non-inferiority of the abbreviated protocol and addressing clinical populations are warranted. Clinical Trials.gov Registration ID: NCT02643927